Hadits dan Hubungannya dngan Al-Qur'an - Agus Rifki Ridwan; Susanti; Aji Saputra (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Hadith and the Koran are two main sources in Islamic teachings which have a close relationship in forming Islamic law and life values. This study aims to examine the textual and contextual relationships between Hadith and the Qur’an from the perspective of tafsir and ushul fiqh. Using qualitative methods and a descriptive-analytical approach, this research found that Hadith functions as an explanation, reinforcement and complement to the verses of the Qur’an. Apart from that, this research also highlights the role of Hadith in clarifying mutasyabihat verses and providing details of general provisions in the Al-Qur’an. Understanding this relationship is important to form the correct frame of mind in understanding Islamic teachings holistically.